ERITEMA MULTIFORME TERKAIT INFEKSI VIRUS DAN ALERGI: LAPORAN KASUS - Alamsyah Piliang; Devi Nasution; Wahyu Hidayat (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2022)
Introduction: Erythema Multiforme (EM) is an acute mucocutaneous inflammatory disease that is self-limiting and manifests itself on the skin, oral mucosa, and another mucosa. Erythema multiforme caused by Herpes Simplex Virus (HSV) infection was diagnosed as Herpes Associated Erythema Multiforme (HAEM). Case and Management: We report a case of EM in a male patient aged 23 years, with a serosanguinous crustal lesion, tend to bleed lips, as well as lesions multiple erosive on the labial mucosa. The patient had a history of fever and symptoms of the prodrome before the lesions appeared, pain when eating and drinking if the lesions appeared. The laboratory test results showed Total IgE: 713.0, IgG HSV1: Positive 100.7, and IgM HSV1: Negative 14.1. Based on the results of the history and clinical examination as well as supporting (IgG and IgE serological tests) a diagnosis of Herpes Associated Erythema Multiforme was made. Treatment with topical corticosteroids, antiseptic mouthwash, multivitamins, and petroleum jelly cream, showed significant improvement and reduction in clinical signs and symptoms in the first week of treatment. Conclusion: The combination of pharmacological and non-pharmacological treatment plays an important role in the advancement of HAEM treatment.